'The next generation of innovation policy: Directionality and the role of demand-oriented instruments'—Introduction to the special section. (28th February 2018) - Edler, Jakob; Boon, Wouter P
Abstract: This editorial introduces the basic idea and content of the special section "the next generation of innovation policy: Directionality and the role of demand side instruments". It highlights the purpose of the special section, i.e. to spark a new debate about innovation policy against the demands for more directionality of policy intervention and the need for policies to actively contribute to system transitions to confront major societal challenges. It summarises the main contribution of each of the articles in the special section.